Do patient-reported outcome scores better identify outlier surgical practice compared with revision rates for total knee arthroplasty? - Morgan C H Lingard; Christopher M A Frampton; Gary J Hooper (Acta Orthopaedica)
Background and purpose:  The New Zealand Joint Registry provides surgeon-level feedback on revision rate and Oxford scores for primary total knee replacement (TKR). Potential outliers are identified using revision rate. Using patient-reported outcome measures to identify outliers, alongside revision rate, could provide a more comprehensive understanding of surgeons’ results. We aimed to evaluate using Oxford scores compared with revision rates to identify potential outliers. Methods: A registry-based prospective longitudinal cohort design was used. The association between surgeon mean Oxford score at 6 months and revision rate at 2 years, within 5 years, and within 10 years was evaluated using the Pearson correlation coefficient. Funnel and scatter plots were used to compare potential outliers for both measures using control limit and centile outlier thresholds respectively. All TKR in the registry prior to 31 December 2021, performed for any indication, were included. Results: There was a weak negative association between mean Oxford score at 6 months and revision rate at 2 years, within 5 years, and within 10 years using the Pearson correlation coefficient. Funnel plot control limits identified similar numbers of outliers for 6-month Oxford score and revision rate, however, there here was minimal overlap in outliers identified using the 2 methods. There was also minimal overlap in outliers using centile thresholds. Conclusion: Correlation between Oxford score at 6 months and revision rates is weaker at the surgeon level compared with the patient level. Mean Oxford score identifies different potential outliers compared with revision rates with minimal overlap. This has implications for reporting surgeon-level outcomes, raising questions regarding the most appropriate measure of surgical performance following TKR.